Molecular analysis of thyroglobulin mutations found in patients with goiter and hypothyroidism - Siffo, Sofía (2017)
Thyroid dyshormonogenesis due to thyroglobulin (TG) gene mutations have an estimated incidence of approximately 1 in 100,000 newborns. The clinical spectrum ranges from euthyroid to mild or severe hypothyroidism. Up to now, one hundred seventeen deleterious mutations in the TG gene have been identified and characterized. The purpose of the present study was to identify and characterize new mutations in the TG gene. We report eight patients from seven unrelated families with goiter, hypothyroidism and low levels of serum TG. All patients underwent clinical, biochemical and image evaluation. Sequencing of DNA, genotyping, as well as bioinformatics analysis were performed. Molecular analyses revealed three novel inactivating TG mutations: c.5560G>T [p.E1835*], c.7084G>C [p.A2343P] and c.7093T>C [p.W2346R], and four previously reported mutations: c.378C>A [p.Y107*], c.886C>T [p.R277*], c.1351C>T [p.R432*] and c.7007G>A [p.R2317Q]. Two patients carried homozygous mutations (p.R277*/p.R277*, p.W2346R/p.W2346R), four were compound heterozygous mutations (p.Y107*/p.R277* (two unrelated patients), p.R432*/p.A2343P, p.Y107*/p.R2317Q) and two siblings from another family had a single p.E1835* mutated allele. Additionally, we include the analysis of 48 patients from 31 unrelated families with TG mutations identified in our present and previous studies. Our observation shows that mutations in both TG alleles were found in 27 families (9 as homozygote and 18 as heterozygote compound), whereas in the remaining four families only one mutated allele was detected. The majority of the detected mutations occur in exons 4, 7, 38 and 40. 28 different mutations were identified, 33 of the 96 TG alleles encoded the change p.R277*. In conclusion, our results confirm the genetic heterogeneity of TG defects and the pathophysiological importance of the predicted TG misfolding and therefore thyroid hormone formation as a consequence of truncated TG proteins and/or missense mutations located within its ACHE-like domain.